2004
DOI: 10.1159/000081974
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Smoking on Serum and Milk of Mothers, and Their Infants’ Serum Insulin-Like Growth Factor-I and Insulin-Like Growth Factor Binding Protein-3 Levels

Abstract: Objective: To investigate the serum and milk in active-smoking and nonsmoking mothers, and their infants’ insulin-like growth factor-I (IGF-I) and insulin-like growth factor binding protein-3 (IGFBP-3) levels. Design and Setting: A cohort study conducted at a tertiary medical center. Subjects: Forty-four mothers (age range: 21–34 years) and their newborns (7 days old) were enrolled in the study. Mothers were interviewed and classified according to their smoking status into one of two groups: the active-smoking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
1
2
0
Order By: Relevance
“…Only a negligible increase in second trimester AFP associated with smoking has been reported [24]. Similarly, the absence of an effect of smoking on first trimester IGFs is in line with observations obtained soon after childbirth [41] or outside pregnancy [36, 28, 42]. …”
Section: Discussionsupporting
confidence: 78%
“…Only a negligible increase in second trimester AFP associated with smoking has been reported [24]. Similarly, the absence of an effect of smoking on first trimester IGFs is in line with observations obtained soon after childbirth [41] or outside pregnancy [36, 28, 42]. …”
Section: Discussionsupporting
confidence: 78%
“…Similar to our findings, Pringle et al [ 22 ] observed that cord plasma IGF-I concentrations were lower in the babies of mothers who smoked, but IGF-II concentrations were unaffected by smoking status. In contrast, Ermis et al [ 23 ] analyzed 44 mother-infant (7-days old) pairs and observed no significant difference in IGF-I concentrations in infant serum samples according to maternal smoking status. The reasons could be due to small sample size and difference in the timing of IGF-I detection (at birth vs. after birth).…”
Section: Discussionmentioning
confidence: 98%
“…Pringle et al [26] showed that maternal tobacco smoking increased levels of GH and IGF-I in the foetus. Ermis et al [10] demonstrated that maternal smoking (5-10 cigarettes/day) did not influence the infant serum levels of IGF-I and IGFBP-3. Likewise we found that maternal smoking (20.1±5.4 cigarettes/day) did not decrease significantly levels of these peptides in the present study.…”
Section: Discussionmentioning
confidence: 99%